Mathematics

 Use factoring to solve the following quadratic:   6x2 + 23x - 18 = 0


Answers

celiagindi

4 years ago Comment

6x²+23x-18=0

(3x-2)(2x+9)=0

Therefore, x=2/3, and x=(-9)/2

CarmelinaTenda681

4 years ago Comment

6x^2+23x-18=0 -- 6*-18=-108 factors that made 23 are 27 and -4

So,
6x^2+27x-4x-18=0 -- factorise each half of the equation i.e. 6x^2+27x and 4x-18
3x(2x+9)-2(2x+9) -- the brackets are the same, that's one side, and combine the 2 other terms outside the brackets for the second bracket.

(3x-2)(2x+9)=0
3x-2=0
3x=2
x=2/3

2x+9=0
2x=-9
x=-9/2

x=2/3 or x=-9/2 -- there we go, fixed.